Determining the Conformational Stability of a Protein from Urea and Thermal Unfolding Curves. Issue 3 (23rd March 2023) - Thurlkill, Richard L.; Trevino, Saul R.; Scholtz, J. Martin; Grimsley, Gerald R.
Abstract: This article contains protocols for determining the conformational stability of a globular protein from either urea or thermal unfolding curves. Circular dichroism is the optical spectroscopic technique most commonly used to monitor protein unfolding. These protocols describe how to analyze data from an unfolding curve to obtain the thermodynamic parameters necessary to calculate conformational stability, and how to determine differences in stability between protein variants. Curr. Protoc. Protein Sci . 71:28.4.1‐28.4.14. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Determining protein conformational stability from urea‐induced unfolding curves Support Protocol 1 : Preparing a urea stock solution Support Protocol 2 : Analyzing urea unfolding curves Basic Protocol 2 : Determining the conformational stability of a protein from thermal unfolding curves Support Protocol 3 : Analyzing thermal unfolding curves Support Protocol 4 : Determining differences in conformational stability for protein variants